A multifunctional biodegradable brush polymer-drug conjugate for paclitaxel/gemcitabine co-delivery and tumor imaging. Issue 7 (12th June 2019) - Sun, Haotian; Yan, Lingyue; Chang, Michael Yu Zarng; Carter, Kevin A.; Zhang, Runsheng; Slyker, Leigh; Lovell, Jonathan F.; Wu, Yun; Cheng, Chong
Abstract : A unique nanosystem enabling paclitaxel/gemcitabine co-delivery and tumor imaging is reported. Abstract : A multifunctional biodegradable brush polymer-drug conjugate (BPDC) is developed for the co-delivery of hydrophobic paclitaxel (PTX) and hydrophilic gemcitabine (GEM) chemotherapeutics, as well as a tumor imaging agent. A novel ternary copolymer of conventional, acetylenyl-functionalized and allyl-functionalized lactides is prepared to serve as the backbone precursor of the BPDC. Acetylenyl groups of the copolymer are then reacted with azide-functionalized poly(ethylene glycol) (PEG) and cyanine5.5, a fluorescent probe, via azide–alkyne click reactions. Subsequently, the allyl groups of the yielded PEG-grafted brush polymer are used to covalently link PTX and GEM onto the backbone via thiol–ene click reactions. The resulting BPDC exhibits an average hydrodynamic diameter of 111 nm. Sustained and simultaneous release of PTX and GEM from the BPDC is observed in phosphate buffered saline, with the release of PTX showing sensitivity under mildly acidic conditions. In vitro studies using MIA PaCa-2 human pancreatic cancer cells illustrate the cellular uptake and cytotoxicity of the BPDC. In vivo, the BPDC undergoes long blood circulation and tumor accumulation, and enables optical tumor imaging. Further development and testing are warranted for multifunctional conjugated brush polymer systems that integrate combination chemotherapy and imaging.